What Young Adults Want: A Multistudy Examination of Vocational Anticipatory Socialization Through the Lens of Students' Desired Managerial Communication Behaviors. (November 2019) - Omilion-Hodges, Leah M.; Shank, Scott E.; Packard, Christine M.
Without experience or in the face of limited work experience, refined expectations for what it means to work or what to expect in terms of communicative role behaviors from a manager may largely be composed of desires. Therein lies the tension; if young adults are unable or unwilling to see work processes and managerial behavior the way that they are, they may reorient their attention from realistic expectations to a focus on their individual desires and preferences. Through a sequential-explanatory mixed-method design (focus groups and exploratory and confirmatory factor analysis), prominent managerial archetypes are explored, categorized, and validated. The archetypes are composed of sets of corresponding communicative and relational behaviors that encompass common approaches to managing. Conversation regarding the overlap and divergence of desires with actual manager communication behaviors may better prepare matriculating students as they transition into the workplace.